Inovação aberta em organização bancária: a técnica Crowdstorming - Almeida, Everton Leonardo de (2020)
Innovation is considered a key source of competitive advantage for organizations. In the banking sector no different, today's dynamic environment requires structures that help banks be more receptive to ideas, demands and environmental change. The fact is that in recent years there has been a great expansion of the opening of companies and governments to innovation associated with the participation of external actors, a phenomenon called open innovation. In this context, this research aimed to analyze the process of implementation and use of the open crowdstorming innovation technique in a banking organization. The object of study was the challenge entitled “Project Bank Ideas” associated with the use of a technology platform for idea management (PrizeIdea®) that took place between December 2017 and April 2018. To respond to the research objective, a survey was carried out. an applied research, descriptive and qualitative and quantitative approach, being based on literature review procedures, documentary research, data analytics and case study. In the context of results, we sought to describe and discuss concepts and activities related to project planning and execution, the main data generated, and the opinion of employees and managers. In conclusion, with the use of the crowdstorming technique associated with the technology platform, employees felt more valued, participation was representative and there was adequate space for discussion and improvement of ideas. We obtained a relevant amount of ideas and interactions (comments and likes) generated on the platform. In addition, in the context of the application, ideas were effectively implemented by the banking organization, despite the lack of communication to employees participating in the challenge about the status of execution of ideas. Overall, after surveying the “Bank of Ideas Project” with the collaborators, it is clear that the realization of the project and participation in the context of open innovation was positive with the sentence that the challenge of ideas should happen associated with the adequate dissemination of the portfolio of ideas selected and effectively put into practice in the context of the organization.